The little tin soldier(big book) - Mott, Lynn (KohWai & Young Publications Kuala Lumpur, 2003)
"The Little Tin Soldier" is a poignant tale that follows the journey of a solitary tin soldier, who is one of a set of 25 but is unique for having a misshapen leg. Despite his limitations, he embodies bravery and love, particularly for a beautiful paper ballerina. The story explores themes of courage, devotion, and the nature of sacrifice as the soldier faces various challenges in his quest to be with the ballerina. Through enchanting storytelling and rich imagery, this timeless fable captures the essence of true heroism and the enduring power of love, inviting readers of all ages to reflect on the beauty of perseverance and the heart's resilience.